Evaluación del rendimiento de pimiento (capsicum annuum) mediante la aplicación edáfica de extractos de algas marinas (ascophyllum nodosum), ácidos húmicos y fúlvicos en la zona de Quevedo. - Vega Lutuala, Wilson Javier (2016)
The demand for food today has led farmers to look for new products or technology that increase levels of performance without damaging the soil, so that the application of products based on seaweed and humic and fulvic acids appears as a option. Considering the above, the present research was carried out in order to evaluate the effect of seaweed and humic and fulvic acids on the agronomic performance and yield of the pepper crop (Capsicum annuum) in the Quevedo area. The trial was carried out at the Experimental La Maria farm at the UTEQ, located at Km 7.5 of the Quevedo - El Empalme road. A randomized complete block design with five treatments in four replicates was used: treatments: Lonite (3 L ha-1), Alga / Tec-WP + Lonite (200g + 1L), Alga / Tec-WP Alga / Tec-WP (200 g) and a Control without application, whose means were compared with the Tukey test at 95% probability. As a main result it was observed that the application of Lonite (3 L ha-1) produced the highest plants at 40 and 60 days after the transplant with 49.08 and 75.85 cm, respectively. When using Alga / Tec-WP + Lonite (200g + 1L), it was obtained less time to flowering, fruits of greater length, diameter and weight, more fruits were produced per plant, higher yield with 50.25 days, 12.83 cm, 50 cm, 133.55 g, 14 fruits per plant and 20625 KgHa-1, in their order. In addition, this treatment generated the highest net income with a total of $ 4548.97 per hectare